INTERPRETING THE CONCEPT OF DOMINUS LITIS: THE ACTIVE ROLE OF JUDGES IN STATE ADMINISTRATIVE COURT - Siti Faridah; Shinta Hadiyantina; Sudarsono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article explores the interpretation and application of the concept of dominus litis—the active role of judges—in the context of the Indonesian State Administrative Court. Unlike the passive adjudicatory model commonly found in civil law systems, the principle of dominus litis in administrative adjudication positions the judge not merely as an arbiter but as a central figure in uncovering the material truth and guiding the resolution of state administrative disputes. Through normative approaches, this study analyzes the legal foundations, limitations, and judicial practices that shape the active role of judges in administrative proceedings. The research further examines how this role aligns with the principles of procedural fairness, legal certainty, and the protection of citizens’ rights against unlawful government actions. Ultimately, the article argues that the appropriate implementation of dominus litis is essential for achieving substantive justice in state administrative adjudication while ensuring that judicial activism remains within constitutional and statutory boundaries.